Pengaruh Digital Marketing Terhadap Peningkatan Pendapatan Usaha Mikro Kecil dan Menengah (UMKM) dalam Perspektif Bisnis Islam: Studi pada UMKM Kecamatan Medan Tembung - Taher, Muhammad Iqbaal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
ABSTRACT In running a business, sellers must be able to think about how their sales can increase every day. Likewise with Micro, Small and Medium Enterprises (MSMEs) which must continue to increase their sales amidst the intense competition. Increased sales can be caused by several factors, one of which is how the seller markets his product. Digital marketing is a method that is widely used today, with various easy access offered to sellers and buyers. In this case, of course, Islamic business views on digital marketing and increasing MSME income can also be reviewed. The aim of this research is to determine the effect of digital marketing on increasing MSME income in Medan Tembung District. This study uses a quantitative approach. Data collection techniques were carried out using observation, questionnaires and interviews. The number of samples in this research was 44 respondents from MSMEs in Medan Tembung Subdistrict. Data was collected through questionnaires. The data analysis techniques used are simple linear regression, partial test (t-test), coefficient of determination test. The research results show that digital marketing has a positive and significant effect on the income of MSMEs in Medan Tembung Subdistrict. Keywords: Digital Marketing, Micro, Small and Medium Enterprises (MSMEs), Islamic Business